STUDI EVALUASI SARANA DAN PRASARANA LABORATORIUM KIMIA SMA NEGERI 5 BENGKULU SELATAN - Marlan Marlan (UNIVERSITAS BENGKULU, 2020)
EVALUATION STUDY OF CHEMICAL LABORATORYFACILITIES AND INFRASTUCTURESMA NEGERI 5 BENGKULU SELATAN ByM A R L A NNIM A2K018059 Study ProgramMagister Administrasi EducationProgram Graduate School of Teaching and Science EducationBengkulu University in 2020, 90 Page ABSTRACT This research is animed to evaluate the facilities and infrastructure of chemistry laboratory SMA Negeri 5 Bengkulu Selatan, witch includes space laboratory, furniture, appliances education, media education, materials consumables wear, and supplies another. This research is used qualitative approach. In the study of this process of evaluation facilities and infrastructure of laboratory chemicals is done by way of doing observation to laboratory chemicals SMA Negeri 5 Bengkulu Selatan and see the condition of the real by referring to the standard of facilities and infrastructure of laboratory chemicals SMA based Permendiknas Number 24 in 2007. So, conduct interviews with heads laboratory chemicals and viewed documents administrative support that exist in the laboratory chemistry. Result of the study showed that the space laboratory chemical SMA Negeri 5 Bengkulu Selatan has been used as a place of activities experiments or utensil laboratory obtained a score of 78,12 % to the category of good, equipment education obtain a score 75,71 % to the category of pretty, media education is already obtain a score of 100 % to the category of good, material discharged wear obtain a score of 80,24 % to the category of good, fixtures others earn a score of 50 % with categories of less well. There is still has a gap between the facilities an infrastructure of laboratory chemicals. The solutions that can be done with the gap this is the fulfillment of the facilities and infrastructure through the budgetary provision with needs of facilities and infrastructure of laboratory chemicals SMA Negeri 5 Bengkulu Selatan. Key word: Facilities and Infrastructure Laboratory of Chemistry